Analysis of the Influence of Village Apparatus Competence, Community Participation, and Internal Control Systems on Village Government Performance - Pranadi, Wempy Bayu; Sudrajat, Sudrajat; Suhendro, Saring (Basecamp Economics PubMed, 2024)
Low budget absorption is a common problem or can be said to be a classic problem in Indonesia because it continues to occur every year. The very large village funds have begun to be a concern for the government, especially regarding the readiness of villages to manage the allocated village funds. This study aims to determine the effect of village apparatus competence, community participation, and internal control systems on village government performance. The population and sample in this study were the village secretary, village treasurer, village representative body, and community representatives. The data collection technique used was through a questionnaire. The instrument was tested using validity tests, reliability tests, and normality tests. The results of this study show that village apparatus competence affects village government performance while community participation and internal control systems do not affect village government performance.